Comparison of SARA Issues Sentiment between Online News Portal and Social Media Towards the 2019 Election - Christiany Juditha (Jurnal Pekommas, 2019)
This study aims to analyze the comparison of SARA (racial/religional) issues sentiment between online news portal and social media. The sentiment analysis method has been applied in this study, by using IMM application during the period of 2018. The results concluded that either in online news portal or social media, SARA issues sentiment have been detected positively during January to August 2018. Generally, negative sentiment on social media tend to be higher compared to online news portal. This condition related to the nature of social media that allows its user to express their opinion freely. The highest percentage of negative sentiment on social media found in January 2018, while it happened a month later in the news portal. It shows that in certain conditions, social media could be more responsive regarding social issues compared to online news portal. Delay response in news portal mainly caused by editorial process and hierarchy system on responding an issue. The initial issue usually has brought up by social media, that followed by news portals in formal manner.